Professional Perspectives on Supporting Those with Alcohol-Related Neurocognitive Disorders: Challenges & Effective Treatment. Issue 3 (3rd July 2021) - Heirene, Robert M.; John, Bev; O'Hanrahan, Marie; Angelakis, Ioannis; Roderique-Davies, Gareth
ABSTRACT: We interviewed health and social care professionals ( n = 17) supporting those with Alcohol-Related Neurocognitive Disorders (ARNDs) to better understand the challenges they face and garner recommendations for effective treatment. Thematic qualitative content analysis was used to systematically analyze interview transcripts. Key challenges associated with treating ARNDs included the challenging behaviors of those with the disorders, their significant physical and mental health needs, stigmatization from others, and a general lack of understanding and awareness of ARNDs. Multiple recommendations for effective treatment were proposed, including first ensuring a comprehensive assessment and diagnostic process is undertaken that informs treatment, multidisciplinary input, and person-specific interventions. ABBREVIATIONS: ARBD: Alcohol-related brain damage: ARND: Alcohol-related neurocognitive disorder: ARD: Alcohol-related dementia: AUD: Alcohol use disorder: DSM: diagnostic & statistical manual of mental disorders: KS: Korsakoff's syndrome: NICE: National Institute for Health and Clinical Excellence: WE: Wernicke's Encephalopathy: WKS: Wernicke's Korsakoff syndrome